Synthesis of boron nitride microtubes and formation of boron nitride nanosheets - Ahmad, P.; Khandaker, Mayeen Uddin; Amin, Yusoff Mohd; Khan, Z.R. (Taylor & Francis, 2015)
Boron nitride microtubes are synthesized in a dual zone quartz tube furnace at 1200°C with ammonia as a reaction atmosphere. Field emission scanning electron microscopy (FE-SEM) results show a unique cone-like morphology of the tubes with larger internal space and thin walls structure. The diameters of the tubes were found to be in the range of 1 to ∼2 µm with the walls thickness estimated to be from 10 to 100 nm. XPS survey shows N 1 s and B 1 s peaks at 398.7 and 191 eV, respectively, that represent h-BN in the sample. Raman spectroscopy indicates a high-intensity peak at 1372.53 (cm−1) that corresponds to the E2g mode of h-BN. Along with the novel tubular morphology of boron nitride microtubes, the present work also explains a mechanism for the formation of boron nitride nanosheets (from boron nitride microtubes) found in the FE-SEM results of the current sample.